2–Benzylidene–1–Indanone Analogues as Dual Adenosine A1/A2a Receptor Antagonists for the Potential Treatment of Neurological Conditions - van Rensburg, HelenaDorathea Janse; Legoabe, LesetjaJ.; Terre’Blanche, Gisella; Van der Walt, MiethaM. (Drug Research, 2019)
Previous studies explored 2-benzylidine-1-tetralone derivatives as innovative adenosine A1 and A2A receptor antagonists for alternative non-dopaminergic treatment of Parkinson’s disease. This study’s aim is to investigate structurally related 2-benzylidene-1-indanones with substitutions on ring A and B as novel, potent and selective adenosine A1 and A2A receptor blockers. 2-Benzylidene-1-indanone derivatives were synthesised via acid catalysed aldol condensation reactions and evaluated via radioligand binding assays to ascertain structure activity relationships to govern A1 and A2A AR affinity. The results indicated that hydroxy substitution at C4 of ring A and meta (3’), or para (4’) substitution on ring B of the 2-benzylidene-1-indanone scaffold (2c) is preferred over substitution at C5 (2d) or C6 (2e) of ring A for adenosine A1 receptor activity and selectivity in the micromolar range. Furthermore, substitution at the meta (3’) position of ring B with chlorine lead to the highly potent and selective adenosine A2A receptor antagonist, compound 2 h. Compound 2c and the 2q behaved as adenosine A1 receptor antagonists in the performed GTP shift assays. In view of these findings, compounds 2c, 2 h, 2q and 2p are potent and selective adenosine A1 and A2A receptor antagonists for the potential treatment of neurological conditions.
Keywords: parkinson’s disease; alzheimer’s disease; 4–hydroxy–2–benzylidene–1–indanones; adenosine antagonists